A tool to enhance occupational therapy reasoning from ICF perspective: The Hasselt Occupational Performance Profile (H-OPP). (4th March 2017) - Ghysels, R.; Vanroye, E.; Westhovens, M.; Spooren, A.
Abstract: Background: In order to enhance occupational therapy reasoning in clinical practice, different elements such as client-centred approach, evidence-based care and interdisciplinary work should be taken into account, but is a challenge. Aim: To describe the development of the digital Hasselt Occupational Performance Profile (H-OPP © ) that enhances occupational therapy reasoning from ICF perspective. Method: A participative qualitative design was used to create the H-OPP © in an iterative way in which occupational therapy lectures, ICF experts, students and occupational therapists in the field were involved. Results: After linking occupational therapy terminology to the ICF, different stages of the H-OPP were identified and elaborated with main features: generating an occupational performance profile based on inventarization of problems and possibilities, formulating an occupational performance diagnosis and enabling to create an intervention plan. In all stages, both the perspectives of the client and the occupational therapist were taken into account. To increase practical use, the tool was further elaborated and digitalized. Conclusion: The H-OPP © is a digital coach that guides and facilitates professional reasoning in (novice) occupational therapists. It augments involvement of the client system. Furthermore, it enhances interdisciplinary communication and evidence-based care.